The Distribution of Property Tax Assessment Inequities in Hamilton - Davies, John Wilfred (My University, 1978)
﻿Multivariate statistical analysis of the ratios of single family dwelling assessed value to current market value or sale price, has been used to evaluate the administration of the property tax assessment function in Hamilton, Ontario. The Hamilton assessment administration has been found to exhibit an unacceptable level of non-uniformity in the assessment of single family dwellings. It is shown that tax burdens will vary substantially within and between price classes of single family dwellings; thus, both horizontal and vertical inequities are attributed to the administration of the assessment function.
The spatial distribution of property tax assessment inequities in Hamilton is presented. It has been shown that certain districts of the city are overassessed relative to others. The spatial pattern is distinct; the area proximate to the industrial waterfront and the central business district have assessment-sales ratios above the mean ratio determined for the city as a whole, while the peripheral or fringe areas of the city are generally characterized by lower assessment-sales ratios.
Keywords: multivariate, market value, tax assessment, Hamilton